2016
DOI: 10.1161/strokeaha.116.013917
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Like Presentation of Primary Angiitis of the Central Nervous System

Abstract: Background and Purpose— We aimed to describe the clinical and imaging features of patients with tumor-like presentation of primary angiitis of the central nervous system. Methods— We retrospectively analyzed 10 patients enrolled in the French primary angiitis of the central nervous system cohort, who initially presented tumor-like brain lesions and compared them with other patients within the cohort. Results— … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 19 publications
2
35
0
Order By: Relevance
“…Conversely, PACNS presenting multiple lesions that also mimic aggressive multifocal cerebral neoplasm have been reported (26, 3134). A retrospective study of 10 tumor-like PACNS cases in France found that the number of patients with single and multiple lesions was similar (4 and 3 patients, respectively) (35). The Mayo Clinic analysis showed that nearly 83% of the multiple lesions tended to be bilateral (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, PACNS presenting multiple lesions that also mimic aggressive multifocal cerebral neoplasm have been reported (26, 3134). A retrospective study of 10 tumor-like PACNS cases in France found that the number of patients with single and multiple lesions was similar (4 and 3 patients, respectively) (35). The Mayo Clinic analysis showed that nearly 83% of the multiple lesions tended to be bilateral (7).…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that 89% of PACNS patients with tumor-like lesions presented lymphocytic patterns, similar to other PACNS subtypes. Granulomatous patterns were next, accounting for approximately 14% (35). Unfortunately, immunohistochemistry and molecular analysis of T-cell and B-cell clonality was not completed in our patient because our neurosurgeons did not doubt the diagnosis of the patient's glioma before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of glucocorticoid and immunosuppressant were the recommended treatment of TLML-PACNS, and aggressive immunosuppressive therapy was associated with improved outcomes compared with glucocorticoids immunotherapy. [10,11] In our study, patients with severe lesion were improved with methylprednisolone and CyP therapy.…”
Section: Discussionmentioning
confidence: 52%
“…Magnetic resonance imaging is the preferred imaging in some hospitals, which shows single stenotic lesions in multiple blood vessels [35]. Steroids and immunomodulators are the preferred treatment that yields good outcomes in comparison to steroids alone [36][37]. There are no clear guidelines for the management of PACNS.…”
Section: Primary Central Nervous System Angiitismentioning
confidence: 99%